The Relationship Between Age, Gender, Nutritional Status, and the Incidence of Acute Respiratory Syndrome (ARI) in Toddlers at Dr. Doris Sylvanus Regional Hospital: Hubungan Antara Usia, Jenis Kelamin, Status Gizi, Dengan Kejadian Ispa Pada Balita Di Rsud Dr. Doris Sylvanus - Deltalis, Mario (Barigas: Medical and Health Science Journal, 2026)
Upper Respiratory Tract Infection (URTI) is a common disease among children under five years old. It acutely infects the upper respiratory tract and is mainly caused by viral or bacterial infections. URTI is typically characterized by symptoms such as runny nose with thickened nasal discharge, cough, fever, sneezing, and sore throat. URTI remains one of the leading causes of morbidity and mortality from infectious diseases worldwide. determine the association between age, sex, and nutritional status with the incidence of URTI among children under five years old at RSUD dr. Doris Sylvanus during the period 2023–2024. This study employed an analytical observational design with a retrospective case-control approach. Data were obtained from medical records of under-five patients diagnosed with URTI and non-URTI. Variables analyzed included age, sex, and nutritional status. Univariate and bivariate analyses were performed using the chi-square test. The results showed a significant association between age and the incidence of URTI among children under five years old (p = 0.039). There was no significant association between sex and the incidence of URTI (p = 0.0578). In contrast, nutritional status showed a significant association with the incidence of URTI (p = 0.004). Age and nutritional status were significantly associated with the incidence of acute upper respiratory tract infection among children under five years old, while sex was not significantly associated. These findings indicate that age and nutritional status play an important role in the occurrence of URTI in children under five. Keywords: children under five, upper respiratory tract infection, age, sex, nutritional status